1992
DOI: 10.1093/bja/68.6.636
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Haemodynamic Effects of Spinal and Extradural Anaesthesia for Elective Caesarean Section

Abstract: Serial haemodynamic investigations were performed in 32 women who were allocated randomly to receive either spinal or extradural anaesthesia for elective Caesarean section. Cardiac output was measured by Doppler and cross-sectional echocardiography at the aortic valve. Doppler flow velocity waveforms were recorded also from the umbilical artery. Preloading with Ringer lactate solution 1 litre increased cardiac output in both groups. After injection of bupivacaine, cardiac output remained increased in the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
1
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 24 publications
3
38
1
2
Order By: Relevance
“…Decreases in cardiac output are more frequent than systemic hypotension during spinal anaesthesia [8]. Clinically, anaesthetists use surrogate indicators such as nausea, vomiting and sudden bradycardia to warn of low cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in cardiac output are more frequent than systemic hypotension during spinal anaesthesia [8]. Clinically, anaesthetists use surrogate indicators such as nausea, vomiting and sudden bradycardia to warn of low cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a surprisingly high incidence of fetal acidosis that is not accompanied by neonatal depression after spinal anaesthesia for Caesarean section [2,3,10]. Mercier et al [33] reported a 63% incidence of foetal acidosis with a prophylactic intravenous infusion of ephedrine in parturients receiving spinal anaesthesia during Caesarean section.…”
Section: ó 2005 Blackwell Publishing Ltdmentioning
confidence: 99%
“…Regional anaesthesia for Caesarean delivery is associated with a high incidence of maternal hypotension [1] and may result in fetal acidaemia due to decreased uteroplacental blood flow [2][3][4]. Commonly used methods to prevent or treat such hypotension include preloading with fluids [5], avoidance of aortocaval compression [6] and the administration of vasopressor drugs [7][8][9][10].…”
mentioning
confidence: 99%
“…The resurgence in popularity of spinal anesthesia for elective Cesarean section notwithstanding, some anesthesiologists would still choose an epidural when it is desirable to avoid hypotension. 22 Elevation of the legs does not reliably protect against a drop in blood pressure following spinal anesthesia for Cesarean section. 2 3 Careful titration of incremental doses of epidural local anesthetic, along with a slower onset of anesthesia, permits better maternal cardiovascular compensation for sympathetic blockade.…”
Section: Commentarymentioning
confidence: 99%